Engineering cytochrome P450cam into an alkane hydroxylase - Bell, S; Orton, E; Boyd, H; Stevenson, J; Riddle, A; Campbell, S; Wong, L (2003)
The haem monooxygenase cytochrome P450cam from Pseudomonas putida has been engineered into an alkane hydroxylase. Active site amino acid residues were substituted with residues that have bulkier and more hydrophobic side-chains. The residues F87, Y96, V247 and V396, which are further away from the haem, were targeted first for substitution in order to constrain the small alkanes n-butane and propane to bind closer to the haem. We found that just two mutations could increase the alkane oxidation activity of P450cam by two orders of magnitude. The F87W/ Y96F/V247L triple mutant was then used as a basis for introducing further substitutions, at the residues T101, L244, V395 and D297 which are closer to the haem, to improve the enzyme/alkane fit and hence the alkane hydroxylase activity. The F87W/Y96F/T101L/V247L mutant oxidised n-butane with a catalytic turnover rate of 755 nmol(nmol P450cam)-1(min) -1, which is comparable to the camphor oxidation activity of the wild-type (1000 min-1). The F87W/Y96F/T101L/L244M/V247L mutant had lower n-butane oxidation activity but the highest propane oxidation rate (176 min-1) of the P450cam enzymes studied. All P450cam enzymes gave 2-butanol and 2-propanol as the only products. Determination of the extent of uncoupling showed that hydrogen peroxide generation was the dominant uncoupling mechanism. The data indicate that further mutations at residues higher up in the active site are required to localise the substrates close to the haem and to reduce substrate mobility. These next-generation mutants will have higher activity, and may be able to catalyse the oxidation of ethane and methane. © The Royal Society of Chemistry 2003.